Parade of the Nome fire department for the July 4th celebration, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Caption on image: "Nome fire department July 4, 1901" Original image in Hegg Album 5, page 4. Original photograph by Eric A. Hegg 1838; copied by Webster and Stevens 313.A